1990
DOI: 10.2307/2061552
|View full text |Cite
|
Sign up to set email alerts
|

Marital stability throughout the child-rearing years

Abstract: Although there is evidence that the number and ages of children influence marital stability, studies have not systematically tracked the risk of marital disruption throughout the child-rearing years. This study uses marital and fertility histories from the June 1985 Current Population Survey to examine this issue. Continuous-time regression models with ages and numbers of children as time-varying covariates are estimated. Net of controls for age at marriage, year of marriage, education, and marital duration, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
0
6

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 27 publications
5
85
0
6
Order By: Relevance
“…Once this is controlled for, the effect of age changes so that higher risks of dissolution are found among very young women and older women, with the lowest risks at ages about 25 years. As expected, women who are in their second or higher order union have a higher probability of splitting up with their partners (Heaton, 1990). This behavioural effect is emphasised when controlling for unobserved heterogeneity.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Once this is controlled for, the effect of age changes so that higher risks of dissolution are found among very young women and older women, with the lowest risks at ages about 25 years. As expected, women who are in their second or higher order union have a higher probability of splitting up with their partners (Heaton, 1990). This behavioural effect is emphasised when controlling for unobserved heterogeneity.…”
Section: Resultssupporting
confidence: 60%
“…The increased stability of unions following the arrival of children is evidence that children do add something positive to the union and/or that children increase the costs of dissolution. Previous studies in developed countries have found that it is more likely for couples without children to divorce (Heaton, 1990;Lillard, 1993). The findings of these studies could not be generalised to Latin American countries.…”
Section: Union Dissolution and Fertility In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…Those that maintain an evolutionary perspective may find it surprising that children affect marital satisfaction nega-tively; it is odd that while one achieves reproductive success, the satisfaction with the relationship that made reproduction a reality-declines. Undoubtedly, rearing children gives rise to marital conflict (HEATON 1990). Nonetheless, it has been argued that a couple that has successfully reproduced together ought to have heightened satisfaction (BERECZKEI and CSANAKY 1996).…”
mentioning
confidence: 99%
“…Once children are introduced, household division of labor and financial strain are commonly sources of disagreement (HEATON 1990). Couples may disagree in the amount and type of care perceived to be needed (MCBRIDE and MILLS 1993) and differential parental participation in childcare can contribute to marital strife (FELDMAN 2000).…”
mentioning
confidence: 99%